Updated attenuation tomography of Japan subduction zone - Wang, Zewei; Zhao, Dapeng (Geophysical journal international, 2019)
SUMMARY We determine an updated model of P- and S-wave attenuation (Qp, Qs) tomography of the Japan subduction zone using an improved inversion scheme, and derive the first Qp/Qs model of the study region. We establish a system of observation t* equations by taking 1/Q values at 3-D grid nodes arranged in the study volume as unknown parameters. This scheme can eliminate model errors caused by ignoring high-order terms of the Taylor expansion in the Q-format scheme adopted by previous studies. The inversion problem is considered as a quadratic programming problem with bound constraints for best fitting the observed t* data in a least-squares sense. The 3-D attenuation model is obtained by using a limited-memory Broyden–Fletcher–Goldfarb–Shanno algorithm for bound constrained optimization. Because this inversion scheme uses bound constraints to avoid negative Q values, damping regularization is not needed, hence the ranges of Qp and Qs values obtained are less affected by human subjectivity. The subducting Pacific and Philippine Sea slabs exhibit high-Q and high Qp/Qs, whereas the mantle wedge beneath the volcanic front and back-arc area shows low-Q and low Qp/Qs. Both Qp and Qs vary in a range of 10–2000, and the Qp/Qs ratio changes from 0.4 to 1.4. Our results reveal a narrow high-Qp/Qs belt that is coincident with the distribution of volcanic and non-volcanic low-frequency micro-earthquakes (M 0.0–2.5), which may reflect high water-saturation anomalies that are probably associated with slab-derived fluids and responsible for the generation of low-frequency micro-earthquakes.